2006
DOI: 10.1063/1.2167051
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cr substitution in Co ferrite (CoCrxFe2−xO4) using Mossbauer spectroscopy

Abstract: Substitution of other metals for Fe in cobalt ferrite has been proposed as a method to tailor the magnetic and magnetoelastic properties for sensor and actuator applications ͓H. Zheng et al., Science 303, 661 ͑2004͔͒. However, to understand the effect of Cr substitution, one needs atomic-level information on the local environments and interactions of the transition-metal ions. In this study, Mossbauer spectroscopy was used to investigate the local environments of the Fe atoms in these materials. A series of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 10 publications
3
27
0
1
Order By: Relevance
“…This indicates the presence of two different types of ferromagnetic Fe atoms in the material, which are identified as Fe in the A ͑tetrahedral͒ and B ͑octahedral͒ sites of the spinel structure. The spectra show a behavior that is observed to be qualitatively similar to that of the Cr-and Mn-substituted cobalt ferrites: 8,9 as the Ga concentration increases, the line spacing ͑indicative of the magnetic hyperfine field at the Fe nuclei and related to the exchange coupling͒ can be seen to decrease and the spacing of the two individual sextets that make up a͒ Electronic mail: krieblek@moravian.edu each spectrum varies relative to one another. Quantitative values for the mean hyperfine field strengths, hyperfine field distribution widths, and isomer shifts of Fe A and B sites in all the samples were calculated by fitting a composite of two hyperfine patterns to each spectrum using WMOSS analysis software.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…This indicates the presence of two different types of ferromagnetic Fe atoms in the material, which are identified as Fe in the A ͑tetrahedral͒ and B ͑octahedral͒ sites of the spinel structure. The spectra show a behavior that is observed to be qualitatively similar to that of the Cr-and Mn-substituted cobalt ferrites: 8,9 as the Ga concentration increases, the line spacing ͑indicative of the magnetic hyperfine field at the Fe nuclei and related to the exchange coupling͒ can be seen to decrease and the spacing of the two individual sextets that make up a͒ Electronic mail: krieblek@moravian.edu each spectrum varies relative to one another. Quantitative values for the mean hyperfine field strengths, hyperfine field distribution widths, and isomer shifts of Fe A and B sites in all the samples were calculated by fitting a composite of two hyperfine patterns to each spectrum using WMOSS analysis software.…”
Section: Resultsmentioning
confidence: 70%
“…4͒, the hyperfine field distribution width increases with increasing Ga content, with the B-site distribution width increasing faster than A. Both the A-site and B-site hyperfine fields decrease at a faster rate for Ga substitution than they do for Mn substitution 8 or even Cr substitution, 9 and the hyperfine field distribution widths increase at a faster rate. Furthermore, the difference in hyperfine field and hyperfine field distribution width between the A-sites and B-sites becomes greater for Ga 3+ substitution than for Mn 3+ or Cr 3+ substitution.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…10 A similar Mössbauer spectroscopy study of Crsubstituted cobalt ferrites showed that Cr 3+ ions have a stronger preference for the B sites than Mn 3+ . 11 Additionally, displacement of Co 2+ ions onto A sites was found to be more prevalent in Cr-substituted cobalt ferrites than in Mnsubstituted cobalt ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently cobalt ferrite based composites have received attention because of their high magnetostriction, high sensitivity of magnetic induction to applied stress, chemical stability and low cost. [9][10][11][12] These make the materials attractive for use in magnetoelastic sensors, 1 and as the magnetoelastic component in oxidebased "multiferroic" composites.…”
Section: Introductionmentioning
confidence: 99%